Minat Belajar Siswa Pada Penerapan Joyful Learning - Rosida, Dewi; Siti Robi'atul Mardliyah; Muhamad Kadarin Jarnawi; Abd. Aziz; Agus Shomad; Wasi'ul Mu'arif (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study examines the application of the Joyful Learning model as a learning strategy to increase student learning interest at Madrasah Tsanawiyah Negeri 1 Klaten. Joyful Learning emphasizes creating a fun, interactive, and meaningful learning atmosphere through educational games, collaborative activities, and contextual learning experiences. This approach was chosen because it can foster intrinsic motivation, self-confidence, and active student participation in the learning process. The study used a qualitative approach with a case study design conducted at Madrasah Tsanawiyah Negeri 1 Klaten. The results showed that teachers implemented Joyful Learning through three main stages: building a positive classroom atmosphere, linking material to students' real experiences, and conducting appreciative learning reflections. The implementation of this model has been proven to increase student learning interest, as indicated by increased enthusiasm, involvement, and curiosity about the material. Obstacles such as limited time, facilities, and minimal teacher training remain major challenges, but Joyful Learning is considered potential as an effective, humanistic, and sustainable learning model in fostering students' enthusiasm for learning.